Search for a Higgs boson in the diphoton final state using the full CDF data set from pp collisions at s=1.96TeV - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2012)
A search for a narrow Higgs boson resonance in the diphoton mass spectrum is presented based on data corresponding to 10fb -1 of integrated luminosity collected by the CDF experiment from proton-antiproton collisions at s=1.96TeV. To increase the sensitivity of the search, we employ a multivariate discriminant technique for the first time in this channel at CDF. No evidence of signal is observed, and upper limits are set on the cross section times branching ratio of the resonant state as a function of the Higgs boson mass. The limits are interpreted in the context of the standard model with an expected (observed) limit on the cross section times branching ratio of 9.9 (17.0) times the standard model prediction at the 95% credibility level for a Higgs boson mass of 125GeV/c 2. Moreover, a Higgs boson with suppressed couplings to fermions is excluded for masses below 114GeV/c 2 at the 95% credibility level. © 2012 Elsevier B.V.